EXTENSIVE READING IN HIGHER EDUCATION: WHY AREN’T ESP TEACHERS DOING IT? - Canda Putri Anggini; Hamka Munir; Denny Hendra Cipta; Ismail Ramli; Halman; Al Amin; Lusy Rahmawati; Siffa Annisa Fitri Ramadhani (e-Journal of ELTS (English Language Teaching Society), 2026)
Extensive Reading is rarely used by the teachers in teaching and learning process in Indonesia. Extensive reading is proved to have many benefits in teaching learning process especially for students. However, many ESP teachers are reluctant to apply the program in the class. This study aims at finding ESP teacher’s attitude towards extensive reading. The subjects of this study are 24 ESP teachers. This study is a qualitative research. The data were collected by using guided interview to the subjects. Then, the data were analyzed by using content analysis. The results of the study indicated that ESP teachers have positive cognitive and conative attitude but negative affective attitude towards extensive reading. Teachers are suggested to raise their awareness on extensive reading and apply it in the class. Other researchers are also suggested to do research in similar topic with wider scope and in different education level.